Wage mobility in Israel: The effect of sectoral concentration - Ana Rute Cardoso; Shoshana Neuman; Adrian Ziderman (Bar-Ilan University, Department of Economics, 2009)
Using a unique eight-year data set, merging population census and national insurance data, the paper examines and compares patterns of wage mobility in Israel. First, the public and the private sectors are compared. Second, within each of these sectors, a distinction is made between sub-sector groupings that exhibit a high level of concentration and those that are more diffuse and unregulated. Based on alternative measures of wage mobility, the central finding of the paper is that the extent of wage mobility in a given economic sector is negatively related to the degree of concentration in that sector.
Keywords: J3; J6; L5; 330; wage mobility; concentration; economic sectors; Israel; Lohnrigidität; Privatwirtschaft; Öffentlicher Dienst; Unternehmenskonzentration; Israel